Analýza vybraného podniktelského subjektu pomocí vybraných metod - Soušková, Šárka (Vysoké učení technické v Brně. Fakulta podnikatelská, 2015)
Diplomová práce je zaměřena na analýzu vybrané společnosti PSG – International a.s., která podniká ve stavebnictví, energetice a petrochemii v tuzemsku a v zahraničí. Na základě vybraných metod – Fundamentální analýza, SLEPTE analýza, Porterův model a SWOT analýza, jsem provedla podrobnou analýzu firmy. Na základě zjištěných poznatků předkládám společnosti vhodná doporučení na zlepšení výkonnosti, efektivity a finanční situace.

This Master´s Thesis is focused on the analysis of the company PSG – International a.s. that operates in the construction, energy and petrochemicals in the Czech Republic and abroad. Based on the selected methods – Fundamental analysis, SLEPTE analysis, Porter´model and SWOT analysis, was performed a detailed analysis of the company. Based on the findings I present appropriate recommendations to improve performance, efficiency and financial situation of the analysed company.
Analysis of the Selected Company by the Selective Methods
Keywords: Fundamentální analýza; SLEPTE analýza; Porterův model; SWOT analýza; Rozvaha; Výkaz zisku a ztráty; stavebnictví; energetika; petrochemie; Fundamental analysis; SLEPTE analysis; Porter´s analysis; SWOT analysis; Balance Sheet; Profit and Loss Statement; construction; energy; petrochemicals